(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The survival skills of Plodia interpunctella, Cadra cautella, Ephestia kuehniella, Corcyra cephalonica larvae have been investigated in laboratory trials. Tests were carried out at three different environmental conditions. C. cephalonica larvae were the most resistant to starvation. Second instar larvae anticipated mould; third instar larvae of the considered species anticipated metamorphosis and in few cases they became adults.